Instructional Praxis of Science Teachers Across Educational Levels in Kidapawan City Amidst Academic Apathy: A Multiple Case Study - Kayla T. Casulla; Jaymie A. Rellon; Gemma N. Kintanar (Research Synergy Foundation, 2026)
This qualitative multiple-case study examined the instructional praxis of selected science teachers in Kidapawan City, Philippines, as they addressed students' academic apathy. Despite the growing concern about academic apathy, local studies remain limited, with existing research focusing on values education, student governance, and their relationship with motivation and academic performance, leaving science classrooms underexplored. Anchored in Schön’s Reflective Practice Model, the study explored how science teachers adapted their instructional strategies, the challenges and opportunities they encountered, and the similarities and differences across the cases. Data were collected through in-depth interviews with five science teachers from selected public and private schools and analyzed using within-case thematic analysis and cross-case analysis. Findings revealed that sustaining student engagement required both teaching strategies and teacher flexibility, as teachers employed interactive questioning, gamification, technology integration, collaborative learning, and relationship-building practices. However, their effectiveness was affected by structural and contextual challenges, including limited resources, student fatigue, diverse learning needs, and institutional constraints. At the same time, opportunities such as professional development, collegial collaboration, and reflective practice help teachers improve their approaches and adapt accordingly. The study highlights that addressing academic apathy requires not only adaptive, student-centered teaching but also supportive institutional conditions, offering insights into science education from junior high school through college.